KAJIAN IDEOLOGI KARYA SASTRA FEMINISME TOKOH PEREMPUAN DALAM NOVEL “CINTA 2 KODI” KARYA ASMA NADIA - Nadha Nuur Annisa Suhendra; Miftahulkhairah Anwar; Evi Susanti (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
Examining feminist literary works is examining, understanding and analyzing literary works through feeling and thinking as connoisseurs of literary arts, which are of the female genre with multi-faceted problems that occur in society. An objective societal perspective on the position of women based on the lens of the millennial era. The purpose of this research is to analyze the female character in the novel "Cinta 2 Kodi" which reveals several aspects of life. As with aspects of social culture, women are not always "second creatures" after men. Women can be equal to men if they try. On the economic side, that is, like men, women can also pursue careers in public service. Women can act both as housewives and as career women. The aspect of religion is that women or men have no obstacles to worship. Success is the result of every process of worship. From the aspect of education, women are considered to have low education because they work as housewives. However, as long as she believed in her abilities they had a bright future like boys. The method in this study used descriptive qualitative, the type of data taken was to describe the status and role of women in society, with comparative case study data variables with genre analysis. The results of this study are the author's partiality towards female characters considering that feminism is seen from various aspects. The object of this study is a representation of the ideology of feminism of the female character in the novel "Cinta 2 Kodi".Keywords: Ideology, Literature, Feminism